Development of heterogeneous base catalyst for transesterification reaction - Norashikin, Mohd Hatta (2010)
Among the many possible clean fuel sources, biodiesel derived from vegetable oil (VO) attracts attention as a promising one for substitution or blending with conventional diesel-based fuels. The current process utilizes alkali hydroxide dissolved in methanol for catalyzing the transesterification. However, the homogeneous catalyst gives a problem to environmental which would be leading the environmentally toxic. Therefore, the heterogeneous base catalyst should be developing to replace the homogeneous base catalyst as prevention. Here, the Calcium Oxide (CaO) loaded on Alumina (CaO/Al2O3) is used as the heterogeneous base catalyst for transesterification of Palm Oil and Methanol. The CaO/Al2O3 was prepared by using impregnation method and calcined at 650°C for 5 hours and characterized by Fourier Transfer Infrared Spectroscopy (FT-IR) and Scanning Electron Microscope (SEM). Both of equipment showed that Calcium Oxide is successfully supported by Alumina which 50% Calcium Oxide loading on Alumina is the best result. Then the catalyst was tested for the transesterification between palm oil and methanol. The transesterification reaction between palm oil and methanol is carried out at different parameter such as reaction temperature, mass ratio of catalyst to oil and molar ratio of methanol to oil. Then, the sample is analyzed using Gas Chromatography (GC). The result showed that the higher conversion of biodiesel is obtained by adding CaO catalyst of 3.5%, reaction temperature of 65°C and molar ratio of methanol to oil of 14:1. The higher total conversion of biodiesel is 48.82%. As a conclusion, the biodiesel conversion increased when there are increase in reaction temperature, amount of catalyst loading and molar ratio of methanol to oil.